High Virulence and Antifungal Resistance in Clinical Strains of Candida albicans - Eric Monroy-Pérez; Gloria Luz Paniagua-Contreras; Pamela Rodríguez-Purata; Felipe Vaca-Paniagua; Marco Vázquez-Villaseñor; Clara Díaz-Velásquez; Alina Uribe-García; Sergio Vaca (Canadian Journal of Infectious Diseases and Medical Microbiology)
Antifungal resistance and virulence properties of Candida albicans are a growing health problem worldwide. To study the expression of virulence and azole resistance genes in 39 clinical strains of C. albicans, we used a model of infection of human vaginal epithelial cells with C. albicans strains isolated from Mexican women with vulvovaginal candidiasis (VVC). The strains were identified by PCR amplification of the ITS1 and ITS2 regions of rRNA. The detection and expression of virulence genes and azole resistance genes MDR1 and CDR1 were performed using PCR and RT-PCR, respectively. All strains were sensitive to nystatin and 38 (97.4%) and 37 (94.9%) were resistant to ketoconazole and fluconazole, respectively. ALS1, SAP4–SAP6, LIP1, LIP2, LIP4, LIP6, LIP7, LIP9, LIP10, and PLB1-PLB2 were present in all strains; SAP1 was identified in 37 (94.8%) isolates, HWP1 in 35 (89.7%), ALS3 in 14 (35.8%), and CDR1 in 26 (66.6%). In nearly all of the strains, ALS1, HWP1, SAP4–SAP6, LIP1–LIP10, PLB1, and PLB2 were expressed, whereas CDR1 was expressed in 20 (51.3%) and ALS3 in 14 (35.8%). In our in vitro model of infection with C. albicans, the clinical strains showed different expression profiles of virulence genes in association with the azole resistance gene CDR1. The results indicate that the strains that infect Mexican patients suffering from VVC are highly virulent and virtually all are insensitive to azoles.